2015
DOI: 10.1371/journal.pone.0144286
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral Therapy, Especially Efavirenz, Is Associated with Low Bone Mineral Density in HIV-Infected South Africans

Abstract: PurposeWe determined the prevalence and correlates of low bone mineral density (BMD) in HIV-infected South Africans as there is a paucity of such data from Africa.MethodsBMD and serum 25-hydroxyvitamin D were measured in HIV-positive participants on antiretroviral therapy (ART) and in those not yet on ART (ART-naïve).ResultsWe enrolled 444 participants [median age 35(IQR: 30, 40) years; 77% women]. BMD was low (z score <-2SD) in 17% and 5% of participants at the lumbar spine and total hip, respectively. Total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 23 publications
3
31
0
3
Order By: Relevance
“…Some of these studies are also limited by retrospective design and lack of an HIV-negative control group. The effects of HIV and ART on bone health and vitamin D status in Sub-Saharan Africa, where the burden of HIV infection lies, and where osteoporotic fracture rates are predicted to rise, (13) are largely unstudied, (14) and, although data are emerging, (15)(16)(17) there are important gaps and an urgent need for targeted research. (14) We have shown, in a cross-sectional study of urban South African premenopausal women which compared those who were HIV-infected but ART-naive with those who were HIV-negative, that there were no significant differences in aBMD or vitamin D status related to HIV status, despite HIV-positive women with low CD4 counts having less body fat than both HIV-positive women with preserved CD4 counts and HIV-negative women.…”
Section: H Uman Immunodeficiency Virus (Hiv) Infection Is Associatedmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of these studies are also limited by retrospective design and lack of an HIV-negative control group. The effects of HIV and ART on bone health and vitamin D status in Sub-Saharan Africa, where the burden of HIV infection lies, and where osteoporotic fracture rates are predicted to rise, (13) are largely unstudied, (14) and, although data are emerging, (15)(16)(17) there are important gaps and an urgent need for targeted research. (14) We have shown, in a cross-sectional study of urban South African premenopausal women which compared those who were HIV-infected but ART-naive with those who were HIV-negative, that there were no significant differences in aBMD or vitamin D status related to HIV status, despite HIV-positive women with low CD4 counts having less body fat than both HIV-positive women with preserved CD4 counts and HIV-negative women.…”
Section: H Uman Immunodeficiency Virus (Hiv) Infection Is Associatedmentioning
confidence: 99%
“…Some of these studies are also limited by retrospective design and lack of an HIV‐negative control group. The effects of HIV and ART on bone health and vitamin D status in Sub‐Saharan Africa, where the burden of HIV infection lies, and where osteoporotic fracture rates are predicted to rise, are largely unstudied, and, although data are emerging, there are important gaps and an urgent need for targeted research …”
Section: Introductionmentioning
confidence: 99%
“…A recent study in South African premenopausal women, all of whom were treatment naïve, did not demonstrate any significant differences in BMD between infected and noninfected women . However, in 444 HIV‐infected South African individuals with a mean age of 35 years, hip BMD was significantly lower in those treated with ART compared to treatment‐naïve individuals, with low vitamin D status and use of efavirenz being significant determinants of lower BMD .…”
Section: Bone Mineral Densitymentioning
confidence: 99%
“…This difference in results may be because of the fact that in the former study, 26 BMDs were not adjusted for confounding effects of smoking status and alcohol consumption unlike in our study. Dave et al 27 determined factors associated with low BMD in HIVinfected South Africans. They reported that exposure to efavirenz or lopinavir-based ART was associated with lower total hip BMD, whereas higher body weight and higher serum VitD concentration were associated with higher total hip BMD.…”
Section: Variable (Mean and Sd)mentioning
confidence: 99%
“…The use of efavirenz-based ART was also independently associated with lumbar spine BMD. 27 Bedimo et al 28 found that HIV-infection and hepatitis C virus infection were significantly associated with low BMD but when the statistical models were adjusted for TDF-use, it greatly diminished the association. Their findings suggested that the effect of HIV-infection on BMD was principally driven by TDF.…”
Section: Variable (Mean and Sd)mentioning
confidence: 99%